Intestinal microbiota and the brain-gut axis - Collins, Stephen (Henry Stewart Talks, 2011)
The interaction between the intestinal microbiota and the brain, The microbiota as a component input determining behaviour, The common occurrence of psychiatric co-morbidity with functional and inflammatory gastrointestinal diseases